Performance of bottle gourd to saline water with drip irrigation method (Indian Journal of Arid Horticulture, 2025)
In the uncommand area of IGNP arid zones of Rajasthan, the ground water availability varies in quality and quantity both with time and space. Most of the ground water is saline or sodic in nature with different magnitudes. Development of technology for efficient and safer utilization of poor quality water for crop production is one of the thrust areas of research, as share of water allocation to agriculture is anticipated to reduce. It can be achieved through drip irrigation. Drip irrigation applies water directly to rhizosphere, thus maintaining high moisture within root zone without excess irrigation. These facts permit use of saline water through drip without risk of injury to crops and high salt concentration buildup near the plants. Use of poor quality water through a properly managed drip system provides advantage of reduced salinity level in the root zone. However, the degree of permissible water salinity for use in drip system depends on water quality, soil properties and salinity tolerance of particular crop. Several researchers have reported that through drip irrigation higher crop yields can be obtained along with considerable saving in irrigation water.
Keywords: salinity; tolerance; irrigation; moisture